An Analysis of Implicatures Found in Whatsapp Stories - Rosyiidah, Afiifah Al (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2020)
This study focuses on implicatures found in the WhatsApp stories. This study aims to find and explain types of implicatures found in WhatsApp stories using the theory proposed by Yule (1996). This study employs qualitative design as the research design. In addition, content analysis is applied to obtain the data in which the writer becomes the key instrument of the study. Interactive data analysis, then, is conducted to analyze and explain the data. The data of the study are taken from WhatsApp stories that appears in the writer’s WhatsApp application. This study shows the findings of the types of implicatures. The data are classified into four types of implicatures: generalized conversational implicatures (5 data), particularized conversational implicatures (7 data), scalar implicature (2 data), and conventional implicatures (1 datum).